Clinical manifestations and risk factors of Streptococcus suis mortality among Northern Thai population: Retrospective 13-year cohort study - Ajaree Rayanakorn (2020)
© 2019 Rayanakorn et al. Purpose: Streptococcus suis (S. suis) is an emerging zoonotic disease mainly in pigs, causing serious infections in humans with high prevalence in Southeast Asia. Despite a relatively high mortality rate, there are limited data regarding the risk factors of this life-threatening infection. Therefore, a 13-year retrospective cohort study in Chiang Mai, Thailand during 2005–2018 was conducted to explore risk factors associated with S. suis mortality and to update the outcomes of the disease. Patients and methods: S. suis positive cases were derived from those with positive S. suis isolates from microbiological culture results and Matrix-Assisted Laser Desorption Ionization Time of Flight (MALDI-TOF). Potential risk factors of mortality were identified using univariate and multivariate logistic regression. Results: Of 133 patients with culture-proven S. suis infection identified, there were 92 males and 41 females. The mean age was 56.47 years. Septicemia (55.64%) was the most common clinical manifestation followed by meningitis (37.59%) and infective endocarditis (25.56%). Alcohol drinking and raw pork consumption were documented in 66 (49.62%) and 49 (36.84%) cases respectively. The overall mortality rate was 12.03% (n=16). According to the multivariate analysis, the independent risk factors for mortality were prolonged bacteremia ≥ 6 days (OR = 43.57, 95% CI = 2.46–772.80, P =0.010), septic shock (OR = 13.34, 95% CI = 1.63–109.03, P =0.016), and direct bilirubin > 1.5 mg/dL (OR = 12.86, 95% CI = 1.91–86.59, P =0.009). Conclusion: S. suis is not infrequent in Northern Thailand, where the cultural food habit of raw pork eating is still practiced. To the best of our knowledge, this is the largest series focusing on risk factors of S. suis mortality which has been conducted in Thailand. Prolonged bacteremia ≥ 6 days, septic shock, and direct bilirubin > 1.5 mg/dL were strong predictors associated with S. suis mortality. The mortality risk factors identified may be further utilized in clinical practice and future research to improve patient outcomes.